Nestle Malaysia Proudly Serves The International Halal Market - New Straits Times, (2008)
Nestle Malaysia has always been at the vanguard of the halal food and beverage industry in the country. The company set new benchmarks when it first established an internal halal committee in the 1980s. Interestingly enough Nestle s halal policy was introduced in 1992 two years before the halal certification by the Department of Islamic Development Malaysia (JAKIM).